20th DASC. 20th Digital Avionics Systems Conference (Cat. No.01CH37219)
DOI: 10.1109/dasc.2001.964213
|View full text |Cite
|
Sign up to set email alerts
|

Are air traffic models chaotic?

Abstract: Network queueing models, including some models of air traffic, exhibit sensitivity to very small changes in the times of events that are nominally simultaneous, such as flight departures (pushbacks). Such models might exhibit chaotic behavior when the ordering of otherwise simultaneous (or closely spaced) departures are changed. This paper explores the question as to whether such models do, indeed, exhibit chaotic behavior, or whether the effect is bounded. study of delays in National Airspace System (NAS) sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…For example, an aircraft arriving late (or early) may not have a gate ready for it at the terminal. Callaham and Wieland [11] demonstrated that just a change in the take-off order of aircraft scheduled to depart at the same time can cause a standard deviation in the variation in the delays experienced in the USA as a manifestation of deterministic chaos of equivalent magnitude to increases by 10% of the capacity of the major airports in the USA. Therefore, scheduling often requires some slack to be built in: reserve crews remain on call, extra time is scheduled for turn-around at the gate, and flight schedules build in the in-flight delays predicted from recent operations.…”
Section: An Overview Of Increasing Air Transportation System Capacitymentioning
confidence: 99%
See 2 more Smart Citations
“…For example, an aircraft arriving late (or early) may not have a gate ready for it at the terminal. Callaham and Wieland [11] demonstrated that just a change in the take-off order of aircraft scheduled to depart at the same time can cause a standard deviation in the variation in the delays experienced in the USA as a manifestation of deterministic chaos of equivalent magnitude to increases by 10% of the capacity of the major airports in the USA. Therefore, scheduling often requires some slack to be built in: reserve crews remain on call, extra time is scheduled for turn-around at the gate, and flight schedules build in the in-flight delays predicted from recent operations.…”
Section: An Overview Of Increasing Air Transportation System Capacitymentioning
confidence: 99%
“…The air transportation system is a large, adaptive and nonlinear system. Many of its components are so intertwined and so close to capacity that any change to one aspect of the system can quickly impact many other aspects (e.g., [11,14]). As a result, the importance of modeling and simulation to design and evaluate proposed changes to the air transportation system has been widely recognized by the larger air transportation community.…”
Section: A Peek Into the Future Of Air Transportation Modeling And Simentioning
confidence: 99%
See 1 more Smart Citation
“…It also tends to assume that people are the only adaptive elements of the system, and those people can be trusted to do the right thing. At this point, few of these assumptions hold true for the National Airspace, 19 and, arguably, NextGen will be even more difficult to reliably validate. The NextGen airspace has been optimized to allow for maximum traffic, and optimized systems are inherently more non-linear.…”
Section: Methodsmentioning
confidence: 99%